Incidence of Aflatoxin M1 in Milk and Milk Products from Punjab, Pakistan, and Estimation of Dietary Intake - Shahzad Zafar Iqbal; Muhammad Waqas; Sidra Latif (Dairy, 2022)
In the present study, 124 samples of milk and milk products were analyzed for the presence of aflatoxin M1 (AFM1), which were purchased from the central cities of Punjab, Pakistan. The analysis was carried out using reverse-phase liquid chromatography, which was equipped with a fluorescence detector. The results showed that 66 samples (53.8%) of raw milk and milk products were found to be contaminated with detectable levels of AFM1 above ≤50 ng/L, and 24.2% of the samples had levels of AFM1 higher than the permissible limit of the European Union (EU; 50 ng/kg). In total, 53.6% of the raw milk, 57.8% of the UHT (ultra-heat-temperature) milk, 45% of the powdered milk, 57.1% of the yogurt, 55.5% of the cheese, and 50% of the buttermilk samples had levels higher than the LOD, i.e., 4 ng/L. The highest mean of 82.4 ± 7.8 ng/kg of AFM1 was present in the positive samples of raw milk. The highest dietary intake of AFM1 was found in infants’ milk (5.35 ng/kg/day), UHT milk (1.80 ng/kg/day), powdered milk (5.25 ng/kg/day), and yogurt (1.11 ng/kg/day). However, no dietary intake was detected in the cheese and butter milk samples used for infants. The results from the undertaken work are beneficial for establishing rigorous limits for AFB1 in animal feed, especially considering the high prevalence rate of hepatitis cases in the central cities of Punjab, Pakistan.